The Pengaruh Electronic Word of Mouth (E-WOM) dan Persepsi Harga terhadap Keputusan Pembelian pada Marketplace Shopee - Putri, Ranny Ismawati; Purbaningrum, Catarina Wahyu Dyah (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2025)
The purpose of this study was to determine whether electronic word of mouth (e-Wom) and price perceptions partially and or simultaneously influence purchasing decisions at the Shopee marketplace. The research location is Gunung Kidul University, Yogyakarta. The analysis method used is descriptive quantitative with non-probability sampling technique with purposive sampling approach. The research instrument used a questionnaire via google form which has been tested for validity and reliability with SPSS 26. The results of the overall validity test of the statement items are valid and reliable. Descriptively, the statement items presented get a score in the agree category. Based on statistical tests, there are no problems in either the classical assumption test, multiple linear regression test or hypothesis testing. This research model is normally distributed based on the Kolmogorov Smirnov and P-Plot tests. There is no multicollinearity because the tolerance value is 0.787> 0.10 and the VIF value is 1.270 < 10.00. The Glejser test results show that there are no symptoms of heteroscedasticity. The r test shows that the correlation between X and Y is 0.462 with a strong or moderate category. The r2 test has a value of 0.214, which means that X1 and X2 are able to explain Y by 21.4%. The t value of X1 and X2> t table, namely 2.598 and 6.003> 1.968. The results of f count> f table, namely 36.312> 3.029. So it can be concluded that partially or simultaneously, e-wom and price perceptions have a significant effect on purchasing decisions on the Shopee marketplace by Gunung Kidul University students. Suggestions for future research with similar titles can use or add other variables that can contribute more to the dependent variable.